Inovasi Seni Mural Sebagai Media Edukasi dan Partisipasi Sosial : Praktik Pengabdian Mahasiswa KKN di Jorong Koto, Nagari Sibakur, Kecamatan Tanjung Gadang, Kabupaten Sijunjung - Pulungan, Ali Basrah; Al-Ghifari, Mohd. Rifqi; Sabrina, Hanifa Syifa; Hasibuan, Mariah; N, Nuraini; Syaputra, Indra (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
A mural is a form of two-dimensional visual art that develops in public spaces as a medium of expression, communication, and education. In Jorong Koto, Nagari Sibakur, Tanjung Gadang Subdistrict, Sijunjung Regency, the mural-making activity was part of a community service program conducted by students of Universitas Negeri Padang through their Community Service Program (KKN). This article aims to describe the process of mural creation, community involvement, and the visual themes portrayed, such as the Indonesian national flag and coffee, which represents one of the local livelihoods. The mural also carries symbolic meaning through the participation of residents and the village head, who contributed by imprinting their handprints on the mural. Data were collected through observation, interviews, and documentation. The results show that the mural not only beautifies the environment but also strengthens the sense of togetherness and local identity of the Jorong Koto community. This activity also demonstrates how art-based innovation can be used as a creative approach in community empowerment.